Examining evidence for neighbourhood variation in the duration of untreated psychosis - Kirkbride, J.B. (Elsevier, 2010)
BACKGROUND: Family involvement in help-seeking is associated with a shorter duration of untreated psychoses [DUP], but it is unknown whether neighbourhood-level factors are also important. METHODS: DUP was estimated for all cases of first-episode psychoses identified over 2 years in 33 Southeast London neighbourhoods (n=329). DUP was positively skewed and transformed to the natural logarithm scale. We fitted various hierarchical models, adopting different assumptions with regard to spatial variability of DUP, to assess whether there was evidence of neighbourhood heterogeneity in DUP, having accounted for a priori individual-level confounders. RESULTS: Neighbourhood-level variation in DUP was negligible compared to overall variability. A non-hierarchical model with age, sex and ethnicity covariates, but without area-level random effects, provided the best fit to the data. DISCUSSION: Neighbourhood factors do not appear to be associated with DUP, suggesting its predictors lie at individual and family levels. Our results inform mental healthcare planning, suggesting that in one urbanised area of Southeast London, where you live does not affect duration of untreated psychosis.